Knowledge and Attitudes Among Sri Lankan Pre-intern Doctors on Nutritional Assessment and Counseling - Mathangasinghe, Yasith; Ranasinghe, D; Padeniya, A (General Sir John Kotelawala Defence University, 2017)
Nutritional assessment and counselling are core clinical skills of a doctor. Our objective was to describe the knowledge and attitudes on nutritional assessment and counselling among pre-intern doctors of Sri Lanka. A descriptive cross sectional study was conducted from August to October 2016. All the pre-intern doctors of Sri Lanka participating in the Good Intern Program 2016 were invited for the study. An online self-administered questionnaire was used. Knowledge and attitudes on nutrition were measured using a validated modified 17- item Nutrition in Patient Care Survey questionnaire. All analyses were conducted on SPSS version 22 with a priori alpha of .05. Of 616 respondents, 57.8% (n=356) were females. The mean age was 26.2±0.8 years. Forty four (7.1%) had participated in some kind of special projects in nutrition. A total of 317 (51.5%) had close friends/relatives with a medical condition which needed greater than normal attention to nutrition. Median knowledge score was 65% (IQR=58%–73%). Median positive attitudes score was 65% (IQR=60%–70%). Although 68.7% (n=423) agreed that nutritional assessment should be included in any routine consultation, 80.8% (n=498) agreed that most pre-intern doctors are not adequately trained to discuss nutrition issues with patients. Spearman’s rank correlation coefficient test found a positive correlation between positive attitudes and self-reported knowledge (rs=.204, n=616, p<.0001). Mann Whitney U tests did not show significant differences of knowledge or attitudes depending on sex (p>.05). Those who participated in some kind of special projects in nutrition had a higher knowledge (U=9499.5, p=.007, r=0.109) and attitudes (U=9267.0, p=.003, r=0.120) scores. Those who had a close friend/relative with a medical condition which needed greater than normal attention to nutrition had higher attitude scores (U=42099.0, p=.014, r=0.099), but there was no significant difference in the knowledge scores (U=43726.0, p=0.096, r=0.067). The internal consistency of the scale (Cronbach’s alpha) was 0.82. In conclusion, perceived knowledge and positive attitudes on nutritional assessment and counselling are inadequate among pre-intern doctors.
Keywords: Nutrition, doctors, self-perceived, counselling, knowledge, attitudes